2001
DOI: 10.1175/1520-0469(2001)058<3639:eochom>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Convective Heating on Movement and Vertical Coupling of Tropical Cyclones: A Numerical Study*

Abstract: The influence of convective heating on movement and vertical coupling of tropical cyclones (TCs) is investigated using a hurricane model with different environmental flows. The authors identify two processes by which convective heating may affect TC motion. One is the advection of symmetric potential vorticity (PV) by heatinginduced asymmetric flow. The other is the direct generation of a positive PV tendency by asymmetric heating, which acts to shift a TC to the region of maximum downward gradient of asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 40 publications
5
72
0
Order By: Relevance
“…As discussed in Wu and Wang (2001b), the HA term in the PVT equation can be approximately written as V 1 × ∇P s − V s × ∇P 1 , where V s is the symmetric component of the tangential wind and V 1 is the wave-number-one component of the asymmetric wind. The first term (HA1) represents the advection of the symmetric potential vorticity component by the asymmetric flow.…”
Section: Horizontal Advectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in Wu and Wang (2001b), the HA term in the PVT equation can be approximately written as V 1 × ∇P s − V s × ∇P 1 , where V s is the symmetric component of the tangential wind and V 1 is the wave-number-one component of the asymmetric wind. The first term (HA1) represents the advection of the symmetric potential vorticity component by the asymmetric flow.…”
Section: Horizontal Advectionmentioning
confidence: 99%
“…Wang (2000, 2001a) evaluated the PVT approach using the output of idealized numerical experiments with a coarse spacing of 25 km and understood the vertical coupling of tropical cyclone circulation under the influence of vertical wind shear. Wu and Wang (2001b) found that convective heating can affect tropical cyclone motion by the heating-induced flow and the positive PVT that is directly generated by convective heating.…”
Section: Introductionmentioning
confidence: 99%
“…During the cyclone evolution, the intensity and track forecast depends largely on the evolution and distribution of the heating rates (Wu and Wang, 2001;Wang, 2009), which is mostly decided by the release of latent heat by the condensate within the system. To examine the associated vertical heating profiles that play an important role in determining intensification, diabatic heating rate (dθ/dt) is calculated.…”
Section: Impact Of Explicit Modelling Of Convection In the High Resolmentioning
confidence: 99%
“…TC movement is primarily determined by large-scale steering plus a minor propagation component [Holland, 1983;Carr and Elsberry, 1990;Wang and Li, 1992]. The propagation component arises from nonlinear interactions among the environmental flow, planetary vorticity gradient, and TC circulation [Holland, 1983;Carr and Elsberry, 1990;Wang and Li, 1992] and from diabatic heating [Wu and Wang, 2001]. Figure 2a shows changes in large-scale steering flows over the period , which are obtained by calculating the linear trends of the zonal and meridional components of the steering flows.…”
Section: Changes In the Overland Durationmentioning
confidence: 99%